Sports equipment design impact on athlete performance - The PR1 Paralympic women's indoor rowing world record - Eikevåg, S. W.; Erichsen, J. F.; Steinert, M. (ISEA Engineering of Sport 14 Conference, 2022)
This paper presents findings from evaluating different designs by testing with a world-class Paralympic athlete during the development of high-performance Paralympic sports equipment. Seat designs for the paralympic rowing PR1 class developed through a new process focusing on maximizing movements and supporting impairments were tested by a world-class athlete on an indoor rowing ergometer and used in the 2021 indoor world rowing championship. Results show that the most performant design increased the individual athlete`s power output by 47.6%, enabling the athlete to set a new world record with a margin of 13 seconds.